Unexpected reactivity of graphene oxide with DBU and DMF. Issue 26 (19th June 2018) - Ramírez-Jiménez, Rafael; Franco, Mario; Rodrigo, Eduardo; Sainz, Raquel; Ferritto, Rafael; Lamsabhi, Al Mokhtar; Aceña, José Luis; Cid, M. Belén
Abstract : Several nitrogen-containing graphene-derived materials have been obtained using DBU and DMF as nitrogen sources, and further employed as heterogeneous catalysts. Abstract : An unusual reaction between GO, DBU and DMF, that typically uses base and solvent, has been thoroughly analyzed providing valuable basic knowledge about the reactivity of GO, which is essential to control functionalization and therefore the properties of graphene derivatives. A combination of characterization techniques, experiments and theoretical calculations allowed us to propose a structure for the materials and a plausible mechanism. The catalytic activity of the new basic materials was also analyzed.